Review: The need for holistic, sector-tailored sustainability assessments for milk− and plant-based beverages - E. Maree; J.N. Blignaut; C.J.L. Du Toit; H.H. Meissner; P. Ederer (Animal)
Sustainable food systems encompass nutrition, the environment and socioeconomics, each aspect requiring unique assessment and consideration. This is especially important in the dairy industry, since livestock contributes 14.5% of global greenhouse emissions while also contributing 49% to global calcium supply and 12% to global protein supply. This necessitates strict measurement to ensure science-based decision-making while producing sustainably, ensuring adequate nutrient supply. This review aimed to identify and evaluate existing measures of sustainability with the goal to generate recommendations for future sustainability measurements. From a nutritional perspective, it identified existing measures such as nutritional life-cycle analysis, hybrid nutrient−rich food index, nutrient−rich food adjusted for adequate intake and nutrient deficiencies, as well as the priority micronutrient density score, as methods which consider broader nutrient profiles and utilise more recent research, and therefore serve as a basis for future models. Major limitations exist in the incorporation of bioavailability or the food matrix effect in such measures, as well as food-group−specific indices. The Prospective Urban Rural Epidemiology healthy diet score also provides promise in serving as an updated version of current dietary guidelines. Environmentally, the life cycle analysis approach forms a detailed basis for environmental footprint assessment, although the practical application thereof in modern agriculture may be cumbersome and may warrant the use of simpler metrics. However, the complexity of sustainability assessments due to differing production methods and system boundaries makes comparisons difficult, which justifies either standardised or contextualised indices. Lastly, socioeconomics which are often measured only via retail price with a focus on economics also deserves consideration of affordability at consumer and producer level by evaluating the effect of the production system on the local and global economy, producer affordability and the potential to improve livelihoods. In conclusion, a localised and holistic measure of sustainability is warranted which is both sector and context−specific and reported in sufficient detail to prevent the masking of poor results due to single metric expressions.